Utilization of GEE for Mapping Land Cover Changes in Settlements Before and After the 2018 Lombok Earthquake in North Lombok Regency - Lia Fitta Pratiwi; Luzianawati; Nuzla Af'idatur Robbaniyyah; Kurnia Ulfa; Muhammad Rijal Alfian (Universitas Airlangga, 2026)
A major earthquake struck Lombok, West Nusa Tenggara, in 2018, causing significant infrastructure damage, including in North Lombok Regency. This study aims to analyze land cover changes in North Lombok Regency before and after the earthquake using Sentinel-2 Level-1C satellite imagery. Through supervised classification using the Maximum Likelihood method, changes in the area of various land cover types, such as Bare Land, Paddy Field, Dense Vegetation, Water Bodies, and Built-up Areas, were identified and analyzed temporally in 2017, 2020, and 2023. The results show that the earthquake caused drastic changes in land cover in the study area, particularly a decrease in the area of dense vegetation and an increase in the area of bare land. These changes indicate significant ecosystem disruption caused by the earthquake. Subsequently, a recovery trend was observed in the 2020-2023 period. Changes in land cover, especially in built-up areas and bare land, are consistent with the earthquake's impact and subsequent reconstruction efforts.